Growth patterns over 2 years after birth according to birth weight and length percentiles in children born preterm - Seulki Kim; Yujung Choi; Seonhwa Lee; Moon Bae Ahn; Shin Hee Kim; Won Kyung Cho; Kyung Soon Cho; Min Ho Jung; Byung Kyu Suh (Korean Society of Pediatric Endocrinology, 2020)
Purpose To analyze growth patterns over 2 years after birth according to preterm infant birth weight and length percentiles. Methods Anthropometric measurements of 82 preterm infants were retrospectively reviewed. Preterm infants with birth weight or length below the 10th percentile were classified as small for gestational age (SGA) (n=19) and those between the 10th and 89th percentile as appropriate for gestational age (AGA) (n=63). The association between the length standard deviation score (SDS) at 2 years of corrected age and clinical factors were analyzed. Results The length SDS of the SGA group was significantly increased at 6 months (-1.30±1.71) and 24 months (-0.97±1.06) of corrected age. The length SDS was lower in the SGA group than those in the AGA group at 6 months (-1.30±1.71 vs. -0.25±1.15, P=0.004), 18 months (-0.97±1.39 vs. -0.03±1.29, P=0.015), and 24 months (-0.97±1.06 vs. -0.29±1.12, P=0.022,). The percentage of children with a length SDS of <-2 (growth failure) at 24 months was 15.8% in the SGA group and 4.8% in the AGA group (P=0.108). Multiple linear regression analysis demonstrated that length at 24 months of corrected age was negatively correlated with birth length below the 10th percentile (coefficient β=-0.91, P=0.001) and duration of stay in the neonatal intensive care unit (NICU) (coefficient β=-0.01, P=0.001). Conclusions Despite the fact that catch-up growth occurs during the early period of infancy in a large portion of preterm SGA infants, a significant portion of these infants show growth failure at 24 months of age. Growth over 2 years after birth is affected by birth length and duration of stay in the NICU in preterm children.